Effectiveness of Family Support In Antiretroviral Therapy and Complications of HIV/AIDS (Clinical Research at the VCT Polyclinic Gambiran Regional Kediri City Hospital) - Anis Khoirin Hayati; Dwi Wahyu Indrawati; Dedi Fardiaz; Joni Haryanto; Agus Hayatal Falah (Eduvest - Journal of Universal Studies, 2024)
HIV/AIDS is a frightening disease for Indonesian society today, so that people with HIV/AIDS often get excessive stigma and discrimination. The design of this study was an observational quantitative study with a cross sectional approach with a research focus directed at analyzing family support and service quality on the utilization of the VCT Poly and compliance of HIV / AIDS patients in undergoing antiretroviral therapy (ARV). at Gambiran Hospital, Kediri City with a sample of 109 respondents taken by Accidental Sampling technique. The results showed that most respondents had sufficient family support, namely 56 respondents (51.4%). Most respondents rated the quality of service in the moderate category as many as 56 respondents (51.4%). Most respondents had moderate utilization as many as 55 respondents (50.5%). Most respondents were not compliant with antiretroviral therapy (ARV), as many as 65 respondents (59.6%). The results of the study using the Path Analysis Test showed a p-value <0.05, so H0 was rejected and H1 was accepted, so it was concluded that there was a significant effect of family support and service quality through the use of VCT Poli on the compliance of HIV / AIDS patients in undergoing antiretroviral therapy (ARV) at Gambiran Hospital, Kediri City. Compliance of HIV / AIDS patients in undergoing antiretroviral therapy (ARV) is influenced by family support, service quality and utilization in the VCT Poly itself. So that patients need to be given good support and improve the quality of services available at the VCT Poly.